CREDIT UNIONS’ ACTIVITY AND FACTORS DETERMINING THE CHOICE OF THEM IN LITHUANIA - Jasevičienė, Filomena; Kėdaitis, Vytautas; Vidzbelytė, Simona (Ekonomika, 2014)
Abstract. In the recent years, the role of credit unions in the financial sector of Lithuania has gradually become more significant. The number of credit unions grew together with their assets, number of members, and deposits. The beginning of a rapid process of credit unions’ establishment and development caused unmeasured risks which led to a suspended activity of several credit unions in 2013. This caused an insignificant migration of credit unions’ shareholders (members) from one union to another, retirements, etc. Although residents haven’t lost the confidence, this fact demands to investigate and analyse the factors determining the choice of a credit union. After a survey of credit union members in Lithuania, the factors most significant for shareholders were determined. Also, the factors least significant for the choice of a credit union were determined, and conclusions and recommendations for managers of credit unions were given. Conclusions and recommendations can help the management to choose the strategy which would result in a higher level of new members’ involvement in the union.Key words: credit union, credit union members, credit union performance, factor analysis, criteria of choice